THE INFLUENCE OF TECHNOLOGY ON SPOKEN LANGUAGE: TEXTING, VOICE ASSISTANTS, AND SPEECH PATTERNS (Web of Technology: Multidimensional Research Journal, 2025)
This article explores the profound impact of technology on spoken language, specifically examining how texting, voice assistants, and emerging speech patterns are shaping modern communication. With the rise of smartphones, social media, and AI-driven technologies, the way people interact verbally has undergone significant changes. Texting, while often regarded as a written form of communication, has influenced spoken language through shorthand, acronyms, and the speed of communication. Voice assistants like Siri, Alexa, and Google Assistant have altered how people express themselves, leading to the emergence of more structured and direct speech patterns. Additionally, advancements in speech recognition technology are fostering new linguistic norms, affecting pronunciation, vocabulary, and conversational tone. This article analyzes these technological shifts, investigating their impact on the fluidity, efficiency, and evolution of spoken language in contemporary society.